Peran Hukum dalam Menjaga Keadilan Sosial di Era Digital - Nanda Arfianto Nugroho; Arif Bijaksana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of digital technology has changed many aspects of people's lives, including in terms of social justice. On the one hand, digitalization opens up access to information and accelerates global connectivity. However, on the other hand, various serious challenges have emerged in law enforcement. Inequality in access to technology, algorithmic bias, and the rise of cybercrime are the main issues that test the resilience of the current legal system. This paper aims to explore how the law can play an effective and responsive role in maintaining social justice in the digital era. With a qualitative approach based on literature studies, this article presents an analysis of various current academic literature discussing law, social justice, and technology. The results show that the legal system must be able to adapt quickly, not only at the regulatory level, but also in institutional structures and community participation. The role of society is key to building inclusive and sustainable digital justice. Therefore, law in the digital era is not enough to be just a set of rules, but must be a tool for social empowerment that is able to respond to the dynamics of the times without abandoning the values ​​of justice. Collaboration between stakeholders and strengthening digital literacy are important elements in creating a digital space that is fair for all.